Compression Characteristics of Solid Wastes as Backfill Materials. (22nd March 2016) - Li, Meng; Zhang, Jixiong; Gao, Rui
Abstract : A self-made large-diameter compression steel chamber and a SANS material testing machine were chosen to perform a series of compression tests in order to fully understand the compression characteristics of differently graded filling gangue samples. The relationship between the stress-deformation modulus and stress-compression degree was analyzed comparatively. The results showed that, during compression, the deformation modulus of gangue grew linearly with stress, the overall relationship between stress and compression degree was approximately nonlinear, and the deformation of gangue was rather large during the initial portion of the test. Gangue sample mixed with Talbot Formula provides the best deformation resistance capacity, followed by fully graded and single-graded gangue samples. For applications, with adjustment of the gradation of filling materials and optimal design of compacting equipment, surface subsidence may be better controlled.